New formyl peptide has the stimulating properties in point of immune system cells - Martynov, A; Romanova, E; Pohorila, M; Shcherbak, O; Sidorenko, T; Igumnova, N; Yukhimenko, V (Annals of Mechnikov's Institute, 2019)
Introduction Tuberculosis infection (TBI) is still one of the major health problems, despite of global intensive medical and pharmaceutical efforts as it is known, in the majority of immunocompetent individuals TBI is repressed by immune system, and as a result we can observe the latent TBI. The main danger hides in unpredictable activation process of latent TBI determining the spreading of infection among population. Now we investigate the ability of new formyl peptide to stimulate phagocytosis completion in vivo. This strategy is explained by the key role of the phagocytosis completion in preventing long-term persistence of M. tuberculosis in macrophage. Formyl peptides are released by microbes and damaged tissues that are perceived as danger signals and is recognized by the innate immune system by formyl peptides receptors expressed on neutrophil granulocytes. Recent studies show that activated formyl peptide receptors (FPR1 and FPR2) trigger a variety of functions, including chemotaxis, degranulation, ROS (reactive oxygen) production and phagocytosis. Materials and methods The ability of new formyl peptide to activate the completeness of phagocytosis by peritoneal macrophages absorbed by them was evaluated in vivo. For reaching the aim of the study we have used peritoneal macrophages obtained from white laboratory male mice 2 months of age, and weight - 22 ± 2 g. Total of 36 animals were randomized on 4 groups:1 Group – (Control) - mice with NaCl solution (0,9 %) injection, (n=11), 2 Group – mice with dexamethasone injection, (n=11), 3 Group - mice with dexamethasone and BCG injection, (n=11), 4 Group - mice with dexamethasone, BCG and formyl peptide injection, (n=11). Animals were kept in vivarium of "Mechnikov institute of Microbiology and Immunology of NAMS of Ukraine" on a standard diet with specified conditions of animal management. Work with laboratory animals was performed according to the rules. The peritoneum macrophages functional activity was assessed by using Staphylococcus phagocytosis test, proliferative activity of lymphocytes - by the level of their spontaneous and FGA-induced transformations in vitro (RBTL), level of receptor’s expression on lymphocytes was examined in reaction of lymphocytes rosette formation with sheep red blood cells. The number of different types of cariocytes in the leukogram was counted morphologically using the light microscope «PrimoStar» (Carl Zeiss, Germany), taking into account not less than 200 cells in the preparation stained with Romanowsky-Gimza stain. Statistical significance was determined by using unpaired t test and one way ANOVA. p< 0,05 was taken as the level of significance. Results and discussion The introduction of the new formyl peptide to mice injected with BCG and dexamethasone promoted increasing of the phagocytic activity of peritoneal macrophages. What is demonstrated by significantly growing of phagocytic and lytic indexes in this group compared to the group of mice that has not obtained the formyl peptide after BCG and dexamethasone administration, (p<0,05). Also, was observed the ex vivo enhancing of FGA-stimulated (by 1,4 times) and spontaneous lymphocyte transformation (by 1,8 times) after the formyl peptide’s administration compared to the appropriate control group, (p<0,05). New formyl peptide is able to promote the expression of receptors on lymphocytes. The percent of receptors expression on lymphocytes has raised by 2,7 times after the formyl peptide's administration in mice with BCG and dexamethasone injections. The formyl peptideadministration has led to the normalization of blood cells count, when their depletion after dexamethasone and BCG injection has taken place. Conclusions The new formyl peptide administration to mice injected with BCG and dexamethasone promotes increasing of the phagocytic activity of peritoneal macrophages, enhance the FGA-stimulated and spontaneous lymphocyte transformation, enhances the level of receptors expression on lymphocytes compared with to the group of mice that has not obtained the formyl peptide after BCG and dexamethasone injection, (p<0,05). The formyl peptideadministration normalizes the blood cells count compared to the appropriate control group, where the total count of leucocytes was decreased and ratio of neutrophils, lymphocytes and eosinophils were characterized by a disproportion.